2009
DOI: 10.1590/s1415-43662009000300004
|View full text |Cite
|
Sign up to set email alerts
|

Extração seqüencial de Mn e Zn em solos em função do pH e adição de cama-de-frango

Abstract: RESUMOA disponibilidade de micronutrientes catiônicos e sua distribuição nas frações do solo, são afetadas por diversos atributos, como pH e teor de matéria orgânica do solo. Avaliaram-se a disponibilidade de Mn e Zn por três extratores químicos e o fracionamento desses elementos, por meio de extração seqüencial, em função da variação do pH e da adição de cama-defrango, em amostras da camada superficial (0 a 10 cm) de um Neossolo Litólico distrófico típico e de um Cambissolo Húmico alumínico da região da Serra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
7
0
3
Order By: Relevance
“…Nonetheless, although plants release acids into the rhizosphere, the buffering character of the organic matter prevents variations of pH. This characteristic is important because, under lower pH conditions, there might be greater availability of heavy metals to plants (Nachtigall et al, 2009). The results found for pH are satisfactory, because very alkaline biosolids require great caution in their application in the soils, since the soil-biosolid mixture must have at least pH 7.0, as established by the CONAMA Resolution 375 (Brasil, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, although plants release acids into the rhizosphere, the buffering character of the organic matter prevents variations of pH. This characteristic is important because, under lower pH conditions, there might be greater availability of heavy metals to plants (Nachtigall et al, 2009). The results found for pH are satisfactory, because very alkaline biosolids require great caution in their application in the soils, since the soil-biosolid mixture must have at least pH 7.0, as established by the CONAMA Resolution 375 (Brasil, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the availability of the elements can be affected, with their liberation into the soil solution or with retention/precipitation (Berton & Nogueira, 2010). Decreased Zn availability with increasing pH is well known and, according to Nachtigall, Nogueirol and Alleoni (2009), this fact is related to the transition of exchangeable Zn to no-exchangeble forms, resulting in precipitation of insoluble forms, such as oxides and organic complex.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, decreasing levels of available Mn in these soils is directly linked to increased sensitivity of the element to the pH change Lopes;Santos, 2007). With the increase of the soil pH, the Mn 2+ cationic form is converted into manganic oxides (Hue;May, 2002) or strongly bound to organic matter (Moreira et al, 2016;Nachtigall;Nogueirol;Alleonni, 2009). On the other hand, Matinhos and Telêmaco Borba, who obtained an increase in Mn availability, showed behavior contrary to other soils with similar clay and organic matter content.…”
Section: The Results Presented Inmentioning
confidence: 99%
“…Comparing the available content of these elements in the control treatment to the soil that received 160 t ha -1 of poultry litter, an increase in availability was observed, of 98; 6,537; 639; 45,726% for Mn, Zn, Na and Cu, respectively (Figure 7). Santos et al (2004) and Nachtigall et al (2009) reported similar results, while Malavolta (1979) proposed the opposite, that pH increases in fact decrease Mn, Zn and Cu availability. The rationale for the results observed herein is that the poultry litter contained 559, 745 and 890 mg kg -1 of Mn, Zn and Cu, respectively (Table 1); thus increases in pH reduced the availability of these elements, while application of high doses suppressed pH effects and increased Mn, Zn and Cu availability.…”
Section: ------------------------------------------------------------mentioning
confidence: 91%